Taking Pluralism and Liberalism Seriously: The Need to Re-understand Faith, Beliefs, Religion, and Diversity in the Public Sphere - Benson, I. T. (Journal for the study of religion, 2010)
How we understand the nature of the public sphere and the fact that all citizens are believers and have faith (but not necessarily religious beliefs and faith) is important to treating all beliefs (including religion) fairly in the public sphere. This article argues for a re-understanding of foundational (but often unexamined) ideas such as “secular” and “secularism”, “faith,” “beliefs,” “diversity” and “liberalism.” It argues that an atheistic or agnostic dominance of the public sphere is unfair and, when the principles are understood properly, unconstitutional. The article examines the law and recent cases in South Africa and Canada against a backdrop of each country’s constitutional provisions, as well as recent philosophical arguments, to suggest that key terms and phrases such as the “separation of church and state” and the relationship between religion and equality need to be re-understood in order for pluralism and liberalism to be properly related to human freedom (understood in its personal and communitarian dimensions) and to be properly protected and encouraged by law and politics.